ANALISIS PENGARUH REPUTASI PERUSAHAAN TERHADAP NIAT PEMBELIAN DAN NIAT UNTUK MEREKOMENDASIKAN (STUDI PADA PT. TELKOM INDONESIA) - Brian Gregory Adhihendra; Reno Firman Anriza Hirianto (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2021)
The development of the technology industry at this time has made many new players appear with a variety of innovative products that they offer. One of the businesses that support technological developments at this time is a home internet connection provider, one of which is PT. Telkom Indonesia. A deep understanding of the company's reputation will be of great use to consumers and marketers alike. Using Benefit-Risk Analysis (BRA) framework, this study focuses on examining the effect of company reputation on purchase intention and intention to recommend. Researchers built this study with quantitative techniques with valid sample data of 200 respondents from all over Indonesia who know about PT. Telkom Indonesia. Using Structural Equation Modeling (SEM) with the help of AMOS 21 software, data analysis found that company reputation had a positive and significant effect on purchase intention and intention to recommend.